Atypical pruritic urticarial papules and plaques of pregnancy-a case report - Devaraj, Navin Kumar; Haley, S. (Rwanda Health Communication Center, 2020)
Pruritic urticarial papules and plaques of pregnancy (PUPPP) typically occur during the first pregnancy in the third trimester [1,2]. Papules and plaques of PUPPP are usually found on the abdomen within the striae associated with pregnancy but can extend to the limbs as well [1,3]. PUPPP is characterized by erythema as well as pruritic papules and plaques. Symptomatic treatment with oral antihistamines and topical corticosteroids preparations is usually offered to the pregnant mother as this eruption usually resolves rapidly within one to two weeks postpartum [2,3]. Persistence of the eruptions post-partum is rare. No risks or detrimental effects have been identified. Therefore, the perinatal outcome is excellent for both the mother and new-born baby [3,4]. This case report will review an unusual case of persistent PUPPP at 12 years post-partum in a 43 years old woman who continued to suffer from abrupt symptomatic outbreaks associated with PUPPP without any clear respite. This is unusual because 90% of PUPPP cases remit spontaneously with no recurrences.